# If tan x = 3/4 and tan b = 2/7 Find tan(a-b)

*print*Print*list*Cite

### 3 Answers

tana = 3/4 tan b = 2/7

We know that:

tan(a-b) = (tan a - tanb)/(1+ tana*tanb)

Let us substitute:

tan(a-b) = (3/4 - 2/7) / [1+ (3/4)*(2/7)]

= (21-8)/28 / (1+ 6/28)

= 13/28 / (34/28)

= 13/34

**==> tan(a-b) = 13/34**

### User Comments

We know that tan(a-b) = ( tan a -tan b)/ (1 +tan a* tan b)

Using tan a = 3/4 and tan b = 2/7

tan(a+b) = ( tan a -tan b)/ (1 +tan a* tan b)

=> ( 3/4 - 2/7) / ( 1 + (2/7)*(3/4))

=> (21/28 - 8/28) / (28/28 + 6/28)

=> 13 / 34

**Therefore tan(a –b) = 13/34**

tan (a-b)

= (tan a - tan b) / (1 + tan a.tan b)

We know that : tan a = 3/4, tan b = 2/7

= (3/4 - 2/7) / [1 + (3/4)*(2/7)]

= (13/28) / (34/28)

= 13/34